The Impact of Airbnb Expansion on Real Estate Speculation in Marseille’s Tourist Areas - Océane L. Chevrier (Law and Economy, 2024)
This paper investigates the impact of Airbnb’s expansion on real estate speculation in Marseille’s tourist areas, particularly focusing on the Old Port and Le Panier districts. By analyzing the correlation between the growth of short-term rental platforms and the increase in property values, the study explores how Airbnb has transformed the housing market, contributing to speculative investment and gentrification. The research examines the reduction in long-term rental housing, the rising cost of property, and the displacement of local residents as key outcomes of Airbnb’s proliferation. Through comparisons with similar European cities such as Paris and Madrid, the paper highlights the socio-economic consequences of Airbnb-driven real estate speculation, including shifts in neighborhood demographics and the loss of affordable housing for low- and middle-income residents. The findings emphasize the need for policy interventions to mitigate the negative effects of short-term rentals on the local housing market, balancing tourism-driven economic growth with the preservation of community stability and housing accessibility.